The Potrayal of Hyperreality in Movie Latency (2024) - Saputra, Arfian Dwi; Fernanda, Andri (Lingual Journal of Language and Culture; Vol 18 No 1 (2025): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2025.v18.i01.p07, 2025)
This research analyzes the construction of hyperreality in the film Latency (2024) through a descriptive qualitative approach by focusing on Baudrillard's (1981) four stages of simulacra. The findings show that the movie gradually builds layers of simulation from the second stage of representation that deviates from reality, the third stage of signs that no longer reference reality but pretend to have a basis, and the fourth stage, hyperreality. This process is seen clearly through key scenes, such as Hana's ability to type with her mind and manipulate virtual objects, which blur the line between real reality and simulation. The climax occurs when Hana does not realize that she has killed her best friend in a VR hypnotic state, illustrating how immersive technology can erode the human ability to distinguish reality. The closing scene, in which Hana laughs in relief as her VR headset is removed, becomes a powerful metaphor for the dangers of hyperreality in the digital age. This research not only confirms Baudrillard's theory but also provides a clear example of how modern technology can lead us to a condition where simulation not only mimics reality, but completely replaces it.